Anthropometric measures do not explain the 2D:4D ratio sexual dimorphism in 7‐year‐old children. Issue 9 (25th June 2022) - Jägetoft, Zebulohn; Unenge Hallerbäck, Maria; Julin, Maria; Bornehag, Carl‐Gustaf; Wikström, Sverre
Abstract: Objectives: Digit ratio (2D:4D) might reflect prenatal testosterone exposure and has been used as a putative marker for androgen related outcomes. However, such associations might be inflicted by confounders. Application of 2D:4D in epidemiological research motivate identification of biological background determinants. We examined sex, anthropometric measures, and maternal factors as determinants of 2D:4D in Swedish 7‐year‐old children. Methods: The study was embedded in the Swedish Environmental, Longitudinal, Mother and Child, Asthma and Allergy (SELMA) pregnancy cohort. A total of 870 pre‐pubertal children, median 7.5 years of age, were studied. A single assessor performed digit measurements from scanned photocopies using computer software. Child anthropometric measurements investigated were hand size, birthweight, recumbent birth length, standing height, weight, BMI, body fat percentage, and waist/hip circumference. Maternal factors included age, pregnancy length, parity, and education. Results: We found a significant sexual dimorphism regarding digit lengths and 2D:4D, boys on average presenting a lower 2D:4D than girls also after adjustment for summed finger lengths and body fatness. In crude analyses, maternal age correlated with 2D:4D across the whole population and in females but not in adjusted models. No other study variables were associated with 2D:4D. Conclusion: Digit ratio showed sexual dimorphism at the age of seven and seems to represent a true sex difference rather than an artifact and bias from hand size, body size or body fat content. Among the rest of our investigated variables, we found no determinants constituting important confounders in future research on 2D:4D ratio.